The use of medicinal plants by the population from the Protected Landscape of "Serra de Montejunto", Portugal - Cidália Vinagre; Sandra Vinagre; Ermelinda Carrilho (BMC, 2019)
Abstract Background Traditional medicine has an important role in local communities, who use plants in the treatment of various diseases. The research of traditional uses of medicinal plants allows us to document and analyze ethnopharmacological practices. This paper reports on an ethnobotanical survey that was conducted in the Protected Landscape of the "Serra de Montejunto", a Portuguese area in the west of the Iberian Peninsula, where these studies were nonexistent. Methods The information was obtained through semi-structured ethnobotanical interviews with 78 informants, who were selected from several zones from the study area to have a representative of the entire landscape, during 2014. Local medicinal uses of plants were identified and grouped into 10 categories through data analysis, in quantitative indices such as the relative frequency citation (RFC), the cultural importance index (CI), and the informant consensus factor (F IC). These were used to evaluate the importance of medicinal plants to the locals. Results In the fieldwork, we found 105 taxa used as medicinal plants which belong to 46 families, where Rosaceae, Asteraceae, Fabaceae, and Lamiaceae are the ones with more diversity. The plants were grouped into 10 categories, where the digestive category is the most cited, with 54 taxa, and the ophthalmological category is the less cited, with only one taxon. Leaves and aerial parts are the components most used. Infusion is the most reported form of preparation, along with the oral administration. Most plants referred in this study are still in use today; only 17 are no longer used at the present time because habits have changed. A catalog of medicinal plants was also drawn up. Conclusion This work enabled us to explore once more our experiences and memories as well as the ancestral use of plants with the goal of expanding ethnopharmacological knowledge. The absence of ethnobotanical studies in this region led us to gather information about useful plants and their applications and benefits. This research helps in the conservation effort of the collective knowledge of medicinal plants for future generations. However, a detailed analysis by body system is still required.